2017
DOI: 10.3906/vet-1611-70
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of bryophyte species against Paenibacillus larvae isolates

Abstract: This study was performed to determine the antibacterial activity of methanol extracts of 23 bryophyte species against Paenibacillus larvae isolates that cause American foulbrood diseases in honeybee larvae. The honey and larva samples were collected from nine different locations of Rize in Turkey. A total of 22 gram-positive spore-forming bacteria were isolated from the larva and honey samples. According to the results of morphological, biochemical, and molecular (16S rRNA gene sequencing) tests, 10 isolates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…In another study, methanol extract of I. alopecuroides, was shown to have an effective antimicrobial effect on P. larve isolates (Sevim et al, 2017). Previous studies confirm the high antimicrobial activity values that this species showed in our study.…”
Section: Discussionsupporting
confidence: 87%
“…In another study, methanol extract of I. alopecuroides, was shown to have an effective antimicrobial effect on P. larve isolates (Sevim et al, 2017). Previous studies confirm the high antimicrobial activity values that this species showed in our study.…”
Section: Discussionsupporting
confidence: 87%
“…In 2013, Cheng showed that ethyl acetate extract of this species stimulates apoptosis and increases oxidative stress in L1210 cells (Cheng et al, 2013). In another study with methanol extract of P. commune, the species have been shown to have an effective antimicrobial effect on P. larve isolates (Sevim et al, 2017). These studies support the high antimicrobial activity that this species exhibited in our study.…”
Section: Discussionsupporting
confidence: 82%
“…Polytrichum commune as moss class consumed as boiled tea was chosen as the study material for this specific study because it is used in the treatment of many diseases such as wound healing, antipyretic, antidotal activity, dissolving kidney and gallbladder stones, antipyretic and antipyretic, and colds (Chandra et al, 2017;Hallingback et al, 2000;Greeshma & Murugan 2018). There are a few reports on the antibacterial, cytotoxicity, and antimicrobial activities of solvent extract of Polytrichum commune grown in different parts of the world including Turkey (Klavina et al, 2015;Nikolajeva et al, 2012;Sevim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Wesołowski and Wierzcholska (2018) showed that moss species selectivity related to water-absorbing function was not the case as the water-uptake ratios did not differ between used and not-used moss species. On the other hand, many bryophyte species are known for their medical properties (antimicrobial, antifungal, antiseptic;Asakawa 2007;Bukvički et al 2012;Sevim et al 2017), and this may be the next reason why those birds are quite choosy when collecting bryophyte, but unfortunately there are practically no studies that examine those properties in tit nests and more studies on this subject would be welcome. In a study where tit nests were vacuum-packed and tested for insulation properties, Deeming and Biddle (2015) suggested tremble-thrusting in tits as a way to add air gaps in the moss-made nest wall.…”
Section: Blue Titmentioning
confidence: 99%